Malonic Acid as A Green and Efficient Catalyst for the Mass-scale Synthesis of Pyrrole Medicinal Drugs - Mohamadpour, Farzaneh (Makara Journal of Science, 2020)
A green and naturally biodegradable malonic acid synthesis of highly substituted dihydro-2-oxopyrrole derivatives has been accomplished via one-pot four-condensation of amines (aromatic or aliphatic), dialkyl acetylenedicarboxylate, and formaldehyde under mild reaction conditions. The notable advantages of the present procedure are a green, low cost, and efficient catalyst; operational simplicity; no need for chromatographic purification steps; short reaction times; and good to high yields.